Geomorphological approach to surficial material evaluation in the Serang River Basin Kulonprogo, Yogyakarta, Indonesia - Sutikno Sutikno (Indonesian Journal of Geography, 1988)
This study deals with the evaluation of surficial material characteristics, based on landform units in the Serang River Basin. The approach concentrates on the use of geomorphological mapping by using aerial photo interpretation and field investigations. The landform units, as defined by geomorphological mapping, was used as sample areas to determine the surficial material characteristics. These characteristics include grain size, sphericity and roundness coefficient. The measurement of the material characteristics in the river bed was based on 100 gravel pebbles systematically sampled along the length profile of the river. During the survey, 14 cross sections were chosen. The potential of the alluvial material resources was estimated by their areal distribution, thichness sedimentary and characteristics.Among landform units in the studied area which contains a large amount of the materials are: natural levees, river terraces, river bed and hill foot slopes. Generally, the river bed materials decrease in grain size downstreams and increase in sphericity and roundness coefficient. In some cross sections a reversal was found to the general tendency. This situation might be due to human activities for getting material for construction. Due to human activities some environmental impacts occur.